Clostridium butyricum therapy restores the decreased efficacy of immune checkpoint blockade in lung cancer patients receiving proton pump inhibitors. (31st December 2022) - Tomita, Yusuke; Goto, Yoshihiko; Sakata, Shinya; Imamura, Kosuke; Minemura, Ayaka; Oka, Kentaro; Hayashi, Atsushi; Jodai, Takayuki; Akaike, Kimitaka; Anai, Moriyasu; Hamada, Shohei; Iyama, Shinji; et al.
ABSTRACT: Oral microbiota is associated with human diseases including cancer. Emerging evidence suggests that proton pump inhibitors (PPIs), which allow the oral microbiome to translocate into the gut, negatively influence the efficacy of immune checkpoint blockade (ICB) in cancer patients. However, currently there is no effective treatment that restores the decreased efficacy. To address this issue, we retrospectively evaluated 118 advanced or recurrent non-small cell lung cancer (NSCLC) patients treated with ICB and analyzed 80 fecal samples of patients with lung cancer by 16S metagenomic sequencing. Clostridium butyricum therapy using C. butyricum MIYAIRI 588 (CBM588), a live biotherapeutic bacterial strain, was shown to improve the ICB efficacy in lung cancer. Thus, we investigated how CBM588 affects the efficacy of ICB and the gut microbiota of lung cancer patients undergoing PPI treatment. We found that PPI treatment significantly decreased the efficacy of ICB in NSCLC patients, however, CBM588 significantly restored the diminished efficacy of ICB and improved survival. In addition, CBM588 prolonged overall survival in patients receiving PPIs and antibiotics together. The fecal analysis revealed that PPI users had higher abundance of harmful oral-related pathobionts and lower abundance of beneficial gut bacteria for immunotherapy. In contrast, patients who received CBM588 had lesser relative abundance of potentially harmful oral-related bacteria in the gut. Our research suggests that manipulating commensal microbiota by CBM588 may improve the therapeutic efficacy of ICB in cancer patients receiving PPIs, highlighting the potential of oral-related microbiota in the gut as a new therapeutic target for cancer immunotherapy.